Pharmacokinetics of post-transplant cyclophosphamide and its associations with clinical outcomes in pediatric haploidentical hematopoietic stem cell transplantation - Kyung Taek Hong; Sungyeun Bae; Yoon Sunwoo; Juyeon Lee; Hyun Jin Park; Bo Kyung Kim; Jung Yoon Choi; Joo-Youn Cho; Kyung-Sang Yu; Jaeseong Oh; Hyoung Jin Kang (Biomarker Research)
Abstract Background Post-transplantation cyclophosphamide (PTCy) has paved the way for the increased use of alternative donors, including haploidentical familial donors, with acceptable engraftment and graft-versus-host disease (GVHD) rates. However, pharmacokinetic studies of PTCy in the pediatric population following myeloablative conditioning regimens are scarce. Methods We conducted a prospective and comprehensive pharmacokinetic analysis of pre- and post-transplantation cyclophosphamide levels in pediatric patients undergoing haploidentical hematopoietic stem cell transplantation (HSCT) using a myeloablative busulfan-based conditioning regimen. A total of 14 samples were collected from each patient. Plasma concentrations of cyclophosphamide and carboxycyclophosphamide were analyzed, and clinical outcomes were recorded. The simulated pharmacokinetic profiles of cyclophosphamide and its metabolites were compared among different age groups using real-world data. Results A total of 15 pediatric patients (median age at HSCT 9.6 years, range 1.6–16.8) were enrolled. Thirteen patients had malignant disease. All patients achieved successful neutrophil engraftment, and the cumulative incidences of grade 2–4 acute GVHD and moderate-to-severe chronic GVHD were 13.3% and 14.7%, respectively. The patterns of cyclophosphamide pharmacokinetic parameters were similar between the pre- and post-HSCT doses. The metabolic ratio increased with subsequent doses of PTCy. Patients with severe veno-occlusive disease showed a higher cumulative area under the curve (AUC) of carboxycyclophosphamide (62.6 vs. 40.2 mg x h/L, P = 0.025), while patients with > grade 3 hemorrhagic cystitis had a higher cumulative AUC of cyclophosphamide (1256.2 vs. 778.2 mg x h/L, P = 0.009). In contrast, there were no notable differences in the pharmacokinetic parameters of cyclophosphamide and carboxycyclophosphamide between the groups with and without acute and chronic GVHD. The AUC of cyclophosphamide and its metabolite were similar in children weighing ≥ 30 kg and the virtual adult population. Conclusions Our study provides insights into the pharmacokinetic profile of cyclophosphamide and its metabolite, carboxycyclophosphamide, in pediatric patients undergoing haploidentical HSCT with PTCy. The intricate interplay between pharmacokinetic parameters and post-HSCT complications suggests the need for tailored adjustments in PTCy dosage, particularly in pediatric patients subjected to myeloablative conditioning regimens.